THE IMPLEMENTATION OF THE SINGING METHOD IN ARABIC VOCABULARY MASTERY OF SIXTH GRADE STUDENTS AT MI DDI PALIRANG - Nengsi, Sri Mulya; Susiawati, Susiawati; Jufri, Jufri (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study is a type of Classroom Action Research (CAR) with the research subjects being the sixth-grade students of MI DDI Palirang, totaling 28 students. The aim of this study is to examine the planning, implementation, and learning outcomes of students in mastering Arabic vocabulary using the singing method. Data collection techniques used in this study include observation, interviews, tests, and documentation. The research was conducted in two cycles, each consisting of two meetings. The results showed that the average vocabulary mastery score of students increased from 79 in the first cycle to 90 in the second cycle. This indicates an 11%-point improvement in students’ Arabic vocabulary mastery. Thus, it can be concluded that the implementation of the singing method in learning can improve Arabic vocabulary mastery among sixth-grade students of MI DDI Palirang.